Sosialisasi Pentingnya Anc (Antenatal Care) Teratur Dalam Mencegah Abortus Spontan Di Masyarakat - Devin, Devin; Leli, Leli; Fauziah, Ayu Bella; Hadijah, Hadijah; Nurmiati, Nurmiati; Ali, St. Aminah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Spontaneous abortion is one of the most common complications of pregnancy, especially among pregnant women who do not receive regular prenatal care. Lack of awareness about the importance of Antenatal Care (ANC) visits is a contributing factor to the low rate of early detection of pregnancy risks. This Community Service Program aims to increase awareness and knowledge among pregnant women, their families, and the broader community about the importance of regular ANC visits as a preventive measure against spontaneous abortion. The outreach activities were conducted in Village X in July 2025 using educational lectures, group discussions, video screenings, and the distribution of informational leaflets. The target audience for the activities included pregnant women, their spouses, and health workers. Evaluation was conducted through pre-tests and post-tests to measure changes in participants' knowledge before and after the activities. The results showed a significant increase in knowledge levels, from 40% before the socialization to 85% afterward. The conclusion of this activity indicates that socialization using a participatory and educational approach is effective in improving community understanding of the benefits of regular ANC check-ups. Therefore, similar activities are highly recommended to be conducted regularly to reduce the incidence of spontaneous abortion in the community.